Population Growth And its Effects on Labour Productivity in Tanzania (Tanzania Journal for Population studies and Development, 2019)
This paper uses macro data to analyse the effects of population growth on economy-wide productivity. Specifically, it looks at how increased labour participation due to change in population size affects productivity. Since labour-intensive technology is dominant in major economic sectors of rural agriculture and urban informal and service sectors, the paper anticipated that an increase in population size would create demographic dividend in the form of increased workforce and higher output per labour. The paper estimates a Cobb Douglas production function using time series data from the censuses of 1967 (12.3m people), 1978 (17.5m people), 1988 (23m people), 2002 (34.4m people), and of 2012 (44.9m people). The results reveal a positive effect of population size on labour productivity, controlling for other production inputs like capital, intermediate inputs, raw materials, and others. The estimated difference in underlying productivity was 30 percent higher in the early 1970s, and peaked in the mid-1970s, reaching 45 percent higher than what we observe in 2012. The paper concludes that there are evidences of positive effects of population growth on the economy through increased output. This calls for the need to consider labour-intensive production when setting up new economic enterprises.